Novel introductions of human-origin H3N2 influenza viruses in swine, Chile - Agüero, Belen Monserrat; Ariyama, Naomi; Berrios, Felipe; Enciso, Nikita; Quezada, Barbara; Medina, Rafael A.; Neira, Victor (Frontiers in Veterinary Science, 2025)
Influenza A virus (IAV) continuously threatens animal and public health globally, with swine serving as a crucial reservoir for viral reassortment and evolution. In Chile, H1N2 and H3N2 subtypes were introduced in the swine population before the H1N1 2009 pandemic, and the H1N1 was introduced from the H1N1pdm09 by successive reverse zoonotic events. Here, we report two novel introductions of IAV H3N2 human-origin in Chilean swine during 2023. Our study reveals a closer relationship between recent human seasonal H3N2 and novel swine strains. Interestingly, one strain maintains all the genes from the original human virus, but the other strain is already a reassortment of human H3N2 and an H1N2 previously observed on the farm. Observing global IAV sequences, a similar pattern was identified in the USA confirming the reverse zoonotic potential of current seasonal human H3N2 strains. These results highlight the importance of ongoing surveillance and reinforcing biosecurity in swine farms. These findings raise questions about their potential impact on viral dynamics in the swine population and public health, underscoring the need for further investigation into the origin and evolutionary dynamics of this emerging swine H3N2 reassortant virus.